Composite current collector, pole piece, new energy battery and electric device

By using the oxygen and carbon concentration gradient of the multi-layer structure and the active metal layer in the composite fluid collection, the bonding force between the polymer base film layer and the conductive metal layer is improved, the problem of metal layer falling off is solved, and the new energy battery is improved Stability and safety.

CN222355152UActive Publication Date: 2025-01-14XIAMEN GUANGPU ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202322684726.9
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-01-14
Estimated Expiration
2033-10-08

AI Technical Summary

Technical Problem

The polymer substrate layer in the composite liquid collecting fluid has poor resistance, which causes the metal layer to fall off in the electrolyte, affecting the stability and safety of new energy batteries.

Method used

Using a multi-layer composite film structure, including a polymer base film layer, an active metal layer, a first conductive metal layer, a second conductive metal layer and an oxidation protection layer, the active metal layer is formed by vacuum coating to enhance the polymer base film layer. The bonding force with the conductive metal layer enhances interface activity using oxygen and carbon concentration gradients.

Benefits of technology

The bonding force between the conductive metal layer and the polymer base film layer is improved, the metal layer is prevented from falling off, the stability and safety of the battery are enhanced, and the metal layer cannot be shedded when the 3M tape is bonded and teared open.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222355152U_ABST
    Figure CN222355152U_ABST
Patent Text Reader

Abstract

The utility model provides a composite current collector, a pole piece, a new energy battery and an electric device. A membrane material of the composite current collector comprises a macromolecule base membrane layer, an active metal layer, a first conductive metal layer, a second conductive metal layer and an anti-oxidation protection layer, the molecules of the high-molecular base film layer only contain carbon atoms and hydrogen atoms, and the molecules of the active metal layer contain metal atoms; the active metal layer has a preset oxygen concentration and is used for oxidizing metal atoms of the active metal layer so as to react with atoms of the macromolecular base film layer; the active metal layer is suitable for adding carbon atoms and is used for increasing the carbon content adjacent to the first conductive metal layer; in the direction of the first conductive metal layer, the metal atom concentration of the active metal layer is gradually reduced in a gradient manner; the prepared active metal layer correspondingly improves the binding force of the macromolecule base film layer and the first conductive metal layer, so that the conductive metal layer is prevented from being torn off and delaminated; moreover, the arrangement in the active metal layer can be directly formed, and no additional process is needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of new energy batteries, and in particular to a composite current collector, a pole piece, a new energy battery and an electrical device. Background Art

[0002] New energy batteries, such as lithium-ion batteries, have been widely used in consumer electronics, electric vehicles and other fields. With the continuous development of the battery industry, current collector structures with better performance are needed.

[0003] At present, composite current collector is a new type of current collector material, which is usually made of a polymer film substrate layer and a conductive metal layer plated on both sides of the polymer film substrate layer, forming a "sandwich structure". Compared with pure metal current collectors, the weight of composite current collectors can be reduced by 50%-80%. At the same time, the thickness of composite current collectors is also reduced by 25%-40% compared with that of pure metal current collectors, so that the space in the battery can be transferred to the electrode active material.

[0004] The presence of the polymer substrate layer in the composite current collector can reduce the temperature rise of the battery, reduce the risk of thermal runaway of the battery, and improve the safety of the battery. The polymer substrate layer in the composite current collector is generally made of polymers such as PET and PP. PET, as a polymer with strong polarity, has a good bonding force with the metal layer. The metal layer composited on it can withstand the adhesion and tearing of 3M brand 600 tape without falling off the metal layer. However, PET has poor chemical resistance, and its mechanical properties will gradually deteriorate after long-term immersion in the electrolyte, eventually leading to rapid failure of new energy batteries.

[0005] PP has good chemical resistance and a melting point of 160-175°C, making it a better choice for composite current collector base films. However, PP does not contain oxygen in its structure and is a non-polar material. Conventional metal layers composited on it are difficult to bond with PP, resulting in poor bonding strength. When the low-viscosity masking adhesive is torn apart, the metal layer will also fall off in a large area. This makes it very easy for the metal layer of the PP-based composite current collector to fall off during subsequent processing, making it impossible to use in new energy batteries. Utility Model Content

[0006] In view of this, the purpose of the present invention is to provide a composite current collector, a pole piece, a new energy battery and an electrical device to solve the above problems.

[0007] The utility model adopts the following scheme:

[0008] The present application provides a composite current collector, comprising a multi-layer composite film material; the film material comprises a polymer base film layer, an active metal layer, a first conductive metal layer, a second conductive metal layer and an anti-oxidation protective layer which are stacked; the polymer base film layer contains only carbon atoms and hydrogen atoms, and the active metal layer is constructed to enhance the bonding strength between the polymer base film layer and the first conductive metal layer to prevent the conductive metal layer from being torn off; wherein the active metal layer contains metal atoms; and the active metal layer forms a preset oxygen concentration for oxidizing its metal atoms to react with the atoms of the polymer base film layer; the active metal layer is suitable for adding carbon atoms to enhance the carbon content adjacent to the first conductive metal layer; along the direction of the first conductive metal layer, the metal atom concentration of the active metal layer decreases gradually; the active metal layer thus configured correspondingly enhances the bonding strength between the polymer base film layer and the first conductive metal layer to prevent the conductive metal layer from being torn off.

[0009] As a further improvement, the active metal layer and the first conductive metal layer are formed on the upper and lower surfaces of the polymer base film layer by vacuum coating, the second conductive metal layer is formed on the first conductive metal layer by acid plating or alkali plating, and the anti-oxidation protective layer is formed on the second conductive metal layer by acid plating or alkali plating.

[0010] As a further improvement, the active metal layer is one or more alloys of nickel, chromium, titanium, or zirconium; the oxygen concentration and carbon content, as well as the metal atom concentration are respectively configured to diffuse smoothly, and are controlled and adjusted by the target material composition of the active metal layer or the coating atmosphere.

[0011] As a further improvement, oxygen source gas is added to the active metal layer or the oxygen concentration gradient in the metal target is increased to increase the interface oxygen concentration, and the oxygen concentration ranges from 10at% to 25at%.

[0012] As a further improvement, the active metal layer corresponds to adding a carbon source gas or increasing the carbon content in the metal target to increase the carbon concentration gradient on the conductive metal layer side, and the carbon content within a predetermined depth on the conductive metal layer side ranges from 3% to 10%.

[0013] As a further improvement, the concentration of each metal atom of the active metal decreases by less than 15% per 20 nm within another predetermined depth on the conductive metal layer side.

[0014] As a further improvement, the polymer base film layer is made of polypropylene PP material with a thickness of 3-6um; and the active metal layer deposited on the polymer film base film layer has a thickness of 10-40nm; and the first conductive metal layer is copper with a thickness of 20-120nm, the second conductive metal layer is copper with a thickness of 0.5-3um, and the thickness of the anti-oxidation protective layer is 10-30nm.

[0015] The present application further provides an electrode sheet, comprising the above-mentioned composite current collector, and an electrode active material layer coated on the surface of the composite current collector.

[0016] The present application also provides a new energy battery, including the above-mentioned electrode.

[0017] The present application also provides an electrical device, comprising the above-mentioned new energy battery.

[0018] By adopting the above technical solution, the utility model can achieve the following technical effects:

[0019] The composite current collector of the present application has an active metal layer set between the polymer base film layer and the conductive metal layer. It has a higher oxygen concentration at the highest concentration point of metal atoms and a higher carbon content on the conductive metal layer side. The concentration gradient of metal atoms is lower at a predetermined depth, thereby improving the interfacial activity, stabilizing the diffusion process, and improving the bonding strength between the active metal layer and the conductive metal layer, so that the 3M tape can be bonded and torn without falling off the metal layer. The oxygen concentration and carbon content of the active metal layer, as well as the metal atom concentration, can be directly formed when the active metal layer is set without adding additional steps. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the structure of a composite current collector according to an embodiment of the utility model;

[0021] Figure 2 It is a drawing of a composite current collector according to an embodiment of the utility model;

[0022] Figure 3 This is a scanning electron microscope image of a composite current collector according to an embodiment of the present invention.

[0023] icon:

[0024] 1-polymer base film layer; 2-active metal layer; 3-first conductive metal layer; 4-second conductive metal layer; 5-anti-oxidation protection layer. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the utility model clearer, the technical scheme in the embodiments of the utility model will be clearly and completely described below in conjunction with the drawings in the embodiments of the utility model. Obviously, the described embodiments are part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the utility model. Therefore, the following detailed description of the embodiments of the utility model provided in the drawings is not intended to limit the scope of the utility model for which protection is sought, but merely represents the selected embodiments of the utility model. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the utility model.

[0026] Combination Figures 1 to 3 , this embodiment provides a composite current collector, including a multi-layer composite film material. The film material includes a polymer base film layer 1, an active metal layer 2, a first conductive metal layer 3, a second conductive metal layer 4 and an anti-oxidation protective layer 5 that are stacked. The polymer base film layer 1 contains only carbon atoms and hydrogen atoms, and the active metal layer is constructed to enhance the bonding force between the polymer base film layer and the first conductive metal layer to prevent the conductive metal layer from being torn off; wherein, the active metal layer 2 contains metal atoms. And the active metal layer 2 forms a preset oxygen concentration for oxidizing its metal atoms to react with the atoms of the polymer base film layer 1. The active metal layer 2 is suitable for adding carbon atoms to increase the carbon content adjacent to the first conductive metal layer 3. Along the direction of the first conductive metal layer 3, the metal atom concentration of the active metal layer 2 decreases in a gradient. The active metal layer 2 equipped in this way correspondingly enhances the bonding force between the polymer base film layer 1 and the first conductive metal layer 3 to prevent the conductive metal layer from being torn off.

[0027] The composite current collector mentioned above has an active metal layer 2 set between the polymer base film layer 1 and the conductive metal layer. It has a higher oxygen concentration at the point with the highest concentration of metal atoms, and has a higher carbon content on the conductive metal layer side. The concentration gradient of metal atoms is lower at a predetermined depth, thereby improving the interfacial activity, stabilizing the diffusion process, and improving the bonding strength between the active metal layer 2 and the conductive metal layer, so that the 3M tape can be bonded and torn without falling off the metal layer. In addition, the oxygen concentration and carbon content of the active metal layer 2, as well as the metal atom concentration, can be directly formed when the active metal layer 2 is set, without adding additional steps.

[0028] like Figure 1As shown, in this embodiment, the active metal layer 2 and the first conductive metal layer 3 are formed on the upper and lower surfaces of the polymer base film layer 1 by vacuum coating, the second conductive metal layer 4 is formed on the first conductive metal layer 3 by acid plating or alkali plating, and the anti-oxidation protective layer 5 is formed on the second conductive metal layer 4 by acid plating or alkali plating.

[0029] Furthermore, the active metal layer 2 is one or more alloys of nickel, chromium, titanium, or zirconium. The oxygen concentration and carbon content, as well as the metal atom concentration, are configured to diffuse smoothly and are controlled and adjusted by the target material composition of the active metal layer 2 or the coating atmosphere.

[0030] Among them, the active metal layer 2 corresponds to adding an oxygen source gas or increasing the oxygen concentration gradient in the metal target material to increase the interfacial oxygen concentration, and the range of the oxygen concentration is between 10at% and 25at%. It can be understood that when the active metal layer 2 is set, a sufficient oxygen atom concentration can partially oxidize the active metal atoms, release reaction energy, and promote the active metal atoms to react with the atoms (carbon atoms and hydrogen atoms) of the polymer base film layer 1 to form a reaction bond. When the active metal layer 2 is set, a high interfacial oxygen concentration can be achieved by adding oxygen or increasing the oxygen content in the active metal target material. When the oxygen concentration is lower than 10at%, the reaction energy is not released enough and the bonding force is not good. When the oxygen concentration is higher than 25at%, the atoms of the active metal are excessively oxidized, and the proportion of metal atoms that react with the atoms of the polymer base film layer 1 is reduced, and the bonding force is also poor.

[0031] Among them, the active metal layer 2 corresponds to adding carbon source gas or increasing the carbon content in the metal target material to increase the carbon concentration gradient on the conductive metal layer side, and the carbon content ranges from 3% to 10% within a predetermined depth on the conductive metal layer side. It should be mentioned that the size of carbon atoms is about 40% smaller than that of metal atoms, and the diffusion ability is stronger. When the active metal layer 2 is set, a high carbon concentration gradient on the metal layer side can be achieved by adding carbon source gas or increasing the carbon content in the active metal target material. When the carbon content on the metal layer side is within the depth of 0 to +100nm, the carbon content is less than 3%. Due to the low concentration, the carbon atom concentration diffusion power is insufficient, and the low carbon concentration gradient formed is not enough to allow the active metal layer 2 to be well combined with the conductive metal layer. When the carbon content on the metal layer side is within the depth of 0 to +100nm, the carbon content is higher than 10%, and the atoms of the active metal layer 2 are too much combined with carbon, and the brittleness of the active metal layer 2 will increase, so that the stress between the metal layer and the base film layer is large, and it is easy to fall off, and the bonding force is not good.

[0032] Wherein, the concentration of each metal atom of the active metal decreases by less than 15% per 20nm within another predetermined depth on the conductive metal layer side. It should be noted that when the metal atoms (such as nickel atoms and chromium atoms) on the conductive metal layer side decrease by more than 15% per 20nm with a depth of +20 to +60nm, the concentration gradient from 20nm to 60nm is too large, and the physical and chemical properties of the surface and subsurface on the conductive metal layer side are greatly different, and delamination will occur between layers. When the metal atoms on the conductive metal layer side decrease by less than 15% per 20nm with a depth of +20 to +60nm, the gradient near the interface is small and stable, the metal layer and the base film layer are well combined, and the physical and chemical properties are similar, and delamination is not easy.

[0033] In the above, at the highest concentration point of metal atoms, the atomic ratio of oxygen concentration is higher than 10%. The atomic ratio of carbon content is higher than 3%, and the closer to the highest concentration point, the higher the carbon content. In particular, due to the regulation of oxygen concentration and carbon content, the metal atom concentration on the conductive metal layer side changes little with a predetermined depth of +20 to +60nm, and diffuses stably, and the average percentage reduction per 20nm is less than 10%.

[0034] Furthermore, the polymer base film layer 1 is made of polypropylene PP material with a thickness of 3-6um. Also, the thickness of the active metal layer 2 deposited on the polymer film base film layer is 10-40nm. Also, the first conductive metal layer 3 is copper with a thickness of 20-120nm, the second conductive metal layer 4 is copper with a thickness of 0.5-3um, and the thickness of the anti-oxidation protective layer 5 is 10-30nm.

[0035] The above-mentioned maximum concentration point and positive and negative values ​​of the depth can be specifically referred to in the experimental data table shown below. The following table further illustrates different embodiments and comparative examples of the present application.

[0036]

[0037]

[0038] In summary, at the point where the concentration of metal atoms on the polymer base film layer 1 is the highest, the oxygen concentration is higher than 10%, as shown in the following table:

[0039]

[0040] The carbon content is high on the conductive metal layer side. Within the depth of 0 to +100nm, the carbon content is higher than 3%. The closer to the highest concentration point, the higher the carbon concentration, as shown in the following table:

[0041]

[0042] The concentration of metal atoms on the conductive metal layer side and the polymer base film layer 1 side changes little with the depth from +20 to +60nm, and the metal atoms (such as nickel and chromium atoms) diffuse more stably, and the average decrease rate per 20nm is less than 15%, as shown in the following table:

[0043]

[0044] In order to prove the authenticity and accuracy of the above experimental data, the metal layer bonding strength of the above embodiments and comparative examples was further tested. Specifically, 3 current collector samples of each embodiment and comparative example were cut and laid flat on a flat glass plate. The sample size was 20cm×30cm and fixed with clamps on all sides. The 3M6 tape was evenly attached to the surface of the sample, and the tape was pressed back and forth 4 times with a pressing force of 1MPa to ensure that there were no obvious bubbles between the tape and the current collector. Then one end of the tape was torn off at a speed of 0.5cm / s at a vertical angle of 180°, and the above test steps were repeated 5 times on both sides of the current collector. Finally, it was confirmed whether the metal layer had fallen off, as shown in the following table:

[0045]

[0046] Therefore, it can be clearly concluded from the above table that, due to the further optimization of the interface component structure, the metal layer of Example 1 and Example 2 can reach a level where it does not fall off, and the effect is particularly significant.

[0047] Among them, this embodiment further provides a pole piece, including the above-mentioned composite current collector, and an electrode active material layer coated on the surface of the composite current collector.

[0048] Among them, this embodiment also provides a new energy battery, including the above-mentioned electrode.

[0049] Among them, this embodiment also provides an electrical device, including the above-mentioned new energy battery.

[0050] The above are only preferred implementations of the present utility model. The protection scope of the present utility model is not limited to the above embodiments. All technical solutions under the concept of the present utility model belong to the protection scope of the present utility model.

Claims

1. A composite current collector, characterized in that: It includes a polymer base film layer, an active metal layer, a first conductive metal layer, a second conductive metal layer and an anti-oxidation protection layer which are stacked in phase; the active metal layer is constructed to enhance the bonding force between the polymer base film layer and the first conductive metal layer to prevent the conductive metal layer from being torn off; the active metal layer is one of nickel, chromium, titanium, or zirconium.

2. The composite current collector according to claim 1, characterized in that: The active metal layer and the first conductive metal layer are formed on the upper and lower surfaces of the polymer base film layer by vacuum coating, the second conductive metal layer is formed on the first conductive metal layer by acid plating or alkali plating, and the anti-oxidation protective layer is formed on the second conductive metal layer by contact with an antioxidant and drying.

3. The composite current collector according to claim 1, characterized in that: The polymer base film layer is made of polypropylene PP material with a thickness of 1-12um; and the active metal layer deposited on the polymer base film layer has a thickness of 3-40nm; and the first conductive metal layer is copper with a thickness of 20-120nm, the second conductive metal layer is copper with a thickness of 0.5-3um, and the anti-oxidation protective layer has a thickness of 3-40nm.

4. A pole piece, characterized in that: It comprises the composite current collector as claimed in any one of claims 1 to 3, and an electrode active material layer coated on the surface of the composite current collector.

5. A new energy battery, characterized in that: Comprising the pole piece as claimed in claim 4.

6. An electrical device, characterized in that: Including the new energy battery as described in claim 5.